The Influence of Flashcard Media on the Reading Comprehension Ability of Fourth Grade Elementary School Students - Lubis, Desi Indriani; Kusumawati, Tri Indah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Reading is one of the fundamental skills that students must master from an early stage of education. Proficient reading skills not only support comprehension across various subjects but also contribute to the development of students’ critical thinking abilities. However, low interest in reading and limited reading comprehension remain significant challenges in elementary education. This study aims to examine the effect of using flashcard media on the reading comprehension skills of fourth-grade elementary school students. The research employed a quantitative approach with a quasi-experimental design. The population consisted of all fourth-grade students, with a total sample of 36 students: 17 in the experimental group and 19 in the control group. Data were collected through pretest and posttest assessments, and analyzed using normality, homogeneity, and hypothesis tests. The findings revealed a significant positive effect of flashcard media on students’ reading comprehension abilities. This study contributes a novel insight into the use of visual media as an effective instructional tool to enhance literacy at the elementary level. The implications suggest that integrating engaging and interactive media, such as flashcards, can serve as an effective pedagogical strategy to improve the quality of reading instruction. Furthermore, this research opens opportunities for the development of similar media in other learning contexts.